A Mean Curvature Regularized Based Model for Demodulating Phase Maps from Fringe Patterns (Communications in Computational Physics, 2018)
We introduce a variational method for demodulating phase maps from fringe patterns. This new method is based on the mean curvature of the level sets ofthe phase surface that is used for regularization. The performance of the method is illustrated with both synthetic and real data.
Keywords: Fringe analysis; interferometry; high-order regularization; variational models.